Green @ Universiti Putra Malaysia: cultivating the green campus culture - Aris, Ahmad Zaharin; Ponrahono, Zakiah; Ishak, Mohd Yusoff; Zamaruddin, Nor Hazlina; Noordin, Nor Kamariah; Varatharajoo, Renuganth; Ideris, Aini (EDP Open, 2018)
This article highlights the University’s strategic plan and institutionalization commitment in cultivating the green campus culture encircling the Green@UPM initiative. It presents a range of insights, lesson learned and way forward of UPM green strategies in continuously nurtures the environmentalfriendly campus atmosphere.